Do Wearable Activity Trackers Increase Physical Activity Among Cardiac Rehabilitation Participants? A SYSTEMATIC REVIEW AND META-ANALYSIS. Issue 4 (July 2021) - Ashur, Carmel; Cascino, Thomas M.; Lewis, Christopher; Townsend, Whitney; Sen, Ananda; Pekmezi, Dorothy; Richardson, Caroline R.; Jackson, Elizabeth A.
Abstract : Purpose: The objective of this study was to review randomized controlled trials (RCT), which included a wearable activity tracker in an intervention to promote physical activity among cardiac rehabilitation (CR) participants, and to conduct a meta-analysis for the outcomes of step counts and aerobic capacity (V˙O2max ). Methods: Eight databases were searched for RCTs that included an activity tracker, enrolled adults eligible for CR, and reported outcomes of step count or aerobic capacity. Mean differences were calculated for outcomes in the meta-analyses. Results: Nineteen RCTs with 2429 participants were included in the systematic review and 10 RCTs with 891 participants were included in the meta-analysis. Meta-analysis of three RCTs using a pedometer or accelerometer demonstrated a significant increase in daily step count compared with controls (n = 211, 2587 steps/d [95% CI, 916-5257]; I 2 = 74.6% and P = .002). Meta-analysis of three RCTs using a pedometer or accelerometer intervention demonstrated a significant increase in V˙O2max compared with controls (n = 260, 2.6 mL/min/kg [95% CI, 1.6-3.6]; I 2 = 0.0% and P < .0001). Meta-analysis of four RCTs using a heart rate monitor demonstrated a significant increase in V˙O2max compared with controls (n = 420, 1.4 mL/min/kg [95% CI, 0.4-2.3]; I 2 = 0.0% and P = .006). Conclusions: Use of activity trackers among CR participants was associated with significant increases in daily step count and aerobic capacity when compared with controls. However, study size was small and variability in intervention supports the need for larger trials to assess use of activity trackers in CR. Abstract : Supplemental Digital Content is Available in the Text.Wearable activity trackers such as pedometers, accelerometers, and heart rate monitors are associated with increases in physical activity and aerobic capacity compared with cardiac rehabilitation alone. However, these randomized controlled trials included small numbers of participants and high variation in trackers use and intervention components, supporting the need for larger trials.